Ectomycorrhizal fungal communities in Nothofagus nervosa [Rauli] : a comparison between domesticated and naturally established specimens in a native forest of Patagonia, Argentina - Fernandez, Natalia Verónica; Marchelli, Paula; Gherghel, Felicia; Kost, Gerhard; Fontenla, Sonia Beatriz (2017)
Due to its overexploitation during the past century, Nothofagus nervosa is currently included in conservation and domestication programs, in which ectomycorrhizas play an important role. We aimed to describe the abundance and diversity of ectomycorrhizal fungi (EcMF) in both domesticated and naturally established N. nervosa specimens, and to analyse the influence of age, seasonality and forest management on EcMF communities. The occurrence of arbuscular mycorrhizas (AM) and dark septate endophytes (DSE) was also investigated. Fungal diversity and taxonomic identification were assessed by morphotyping and subsequent ITS-rDNA sequencing. Plant age, seasonality and forest management influenced EcMF communities. Colonization rates were higher than 90 % in all the specimens, and were significantly higher in mature trees and in autumn. The highest EcMF richness and diversity values were registered in domesticated specimens and in autumn. Most EcMF were basidiomycetes, belonging mainly to the Cortinariaceae and Tricholomataceae. Arbuscular mycorrhizas were not detected, while DSE were present within N. nervosa roots. Our results and previously published reports showed that some EcMF are capable of colonizing different Nothofagus species. In addition, the EcMF described in natural ecosystems are different from those colonizing N. nervosa during its cultivation in the nursery. These results improve our understanding of key factors affecting EcMF communities associated with Nothofagus in native forests and nurseries (age, season, forest management, cultivation techniques), and this information is relevant for improving domestication programs.